Development of Supply Chain Quality Management in Peruvian Blueberry Companies: A Case Study in CaÃ±ete, Peru - Edgar D. Ramos; Jean Pierre Yanayaco; Tamy Hinostroza; Ron Mesia (International Journal of Supply Chain Management, 2019)
The keen research objective is to develop a quality system in the Supply Chain Management geared to the agribusiness sector. The Supply Chain Quality Management (SCQM) proposed for blueberry companies must improve their operational performance. This study includes micro and small agricultural enterprises located in the Caete region of Peru, where thanks to the interviews and questionnaires, it was possible to determine the critical practices, which will be applied in the agribusiness sector. An important point of this research is the literature review found to enrich the methodical procedures that are the most important practices of the innovative SCQM model. The research shows that the critical practices to develop the quality management in this sector are Customer Relationship Management, Supplier Relationship Management, Process Management and Human Resources Management. These correctly designed and implemented practices will lead to operational improvement and other qualitative advantages. This research turns out to be completely innovative because the use of the recently proposed technique of Quality Management into the Supply Chain combined with the best practices will be very useful knowledge to the agribusiness sector. The implementation and development of quality systems for the main practices of SCQM is a differentiating factor that is rare to find in similar research. On the other hand, the development of the Peruvian case study focused on the blueberry industry provides great practical value to supply chain operations management of quality. Finally, the knowledge embedded in SCQM applied to small blueberry companies in an emerging country can provideadded value to management to increase the competitiveness of the agribusiness sector.